Hepatitis B virus and cytomegalovirus coinfection in an older patient: a case report - Huimin Liu; Jiaqi Wang; Wenting Chen; Li Jiang; Qing Mao (Journal of International Medical Research, 2024)
Cytomegalovirus (CMV) infection involving the skin is relatively rare. We herein report a case involving a man in his late 70s with positive hepatitis B surface antigen who presented with multiform skin lesions, including a papuloid rash, papular urticaria, and purpura. The patient had taken no antiviral drugs for nearly 13 years but had recently developed severe liver injury. Laboratory examination revealed positive CMV immunoglobulin M, CMV polymerase chain reaction result of 1.09 × 10 2 copies/mL, and a slightly decreased CD4+ cell count; however, the CD8+ T-cell count was within the normal range. A skin biopsy was performed in the region of the papular eruption on the left inner thigh, and the pathologic findings were consistent with CMV infection. After admission, the patient began a combination of antiviral therapy for hepatitis B virus and CMV. After 3 weeks of treatment, the patient was discharged with skin lesions, and his liver function recovered.